Phenotypes of Late-Onset Transthyretin Amyloid Neuropathy: A Diagnostic Challenge. Issue 1 (September 2019) - Živković, Saša A.; Mnatsakanova, Diana; Lacomis, David
Abstract : Abstract: Hereditary transthyretin amyloidosis (hATTR) is a rare cause of severe neuropathy, typically with progressive sensorimotor and autonomic manifestations. The clinical course is marked by progressive worsening with typical survival of 7–11 years following the onset of symptoms. The phenotype may resemble other types of neuropathy, and dysautonomia may be absent at onset delaying the diagnosis. Two medications were recently approved for treatment of hATTR neuropathy in the United States and more may follow. Three major phenotypes of hATTR include neuropathic, cardiac, and mixed. Diagnostic clues include "red-flag" symptoms reflecting typical multisystem involvement, often presenting with cardiomyopathy, gastrointestinal dysmotility, or kidney insufficiency. We present a case series of 4 patients with late-onset hATTR neuropathy who were initially diagnosed with vasculitic neuropathy and chronic inflammatory demyelinating polyneuropathy to illustrate diagnostic challenges encountered with hATTR. Early diagnosis is even more urgent now given the availability of disease modifying treatments.